Treatment with pCramoll Alone and in Combination with Fluconazole Provides Therapeutic Benefits in C. gattii Infected Mice - Jandú, Jannyson J.; Costa, Marliete C.; Santos, Julliana R. A.; Andrade, Fernanda M.; Magalhães, Thais F.; Silva, Márcia V.; Castro, Maria C. A. B.; Coelho, Luanna C. B. B.; Gomes, Aline G.; Paixão, Tatiane A.; Santos, Daniel A.; Correia, Maria T. S. (Frontiers in Cellular and Infection Microbiology, 2017)
Cryptococcus gattii is one of the main causative agents of cryptococcosis in immunocompetent individuals. Treatment of the infection is based on the use of antimycotics, however, the toxicity of these drugs and the increase of drug-resistant strains have driven the search for more effective and less toxic therapies for cryptococcosis. pCramoll are isolectins purified from seeds of Cratylia mollis, a native forage plant from Brazil, which has become a versatile tool for biomedical application. We evaluated the effect of pCramoll alone and in combination with fluconazole for the treatment of mice infected with C. gatti. pCramoll alone or in combination with fluconazole increased the survival, reduced the morbidity and improved mice behavior i.e. neuropsychiatric state, motor behavior, autonomic function, muscle tone and strength and reflex/sensory function. These results were associated with i) decreased pulmonary and cerebral fungal burden and ii) increased inflammatory infiltrate and modulatory of IFNγ, IL-6, IL-10 and IL-17A cytokines in mice treated with pCramoll. Indeed, bone marrow-derived macrophages pulsed with pCramoll had increased ability to engulf C. gattii, with an enhanced production of reactive oxygen species and decrease of intracellular fungal proliferation. These findings point towards the use of pCramoll in combination with fluconazole as a viable, alternative therapy for cryptococcosis management.